(untitled) (Khairulummah, 2022)
The rise of e-commerce, a colossal growth and a significant increase has occurred in all aspects of business life throughout the world. The conducting of business activities via the Internet, specifically, has played a vital role in the development of business and economical sectors in different parts of the world. Primarily, business activities conducted electronically were not specifically regulated because it was generally perceived that regulations may disturb and hinder the expansion of electronic commerce. However, as a result of the remarkable growth of electronic market activities globally, many legal disputes and concerns have raised. This demonstrates the need for regulation to govern the new activities. It is essential for Muslims to implement Islāmic rules in every aspect of their life including commercial ones. From a purely business point of view, Islām has provided its followers with general guidelines which must not be ignored or infringed. This research paper is meant to study the Islāmic perspective in e-commerce, particularly in its transactions. Issues on the legality of e-commerce in Islām are examined to expose to the Muslims around the world so that they could benefit from this new technology if it is proved legitimate and acceptable in Islām.